Family conditions that favor the permanence of accompaniment in the treatment of cancer patients in Solca, Portoviejo - Gorozabel, Lady (2020)
The family during the illness and hospitalization of a relative with an oncological diagnosis, plays an essential role in providing the accompaniment in their treatment process, since that support will help them in their improvement and strength to fight for their lives. The objective of the study is to characterize the family conditions that favor the accompaniment in the treatment of cancer patients. For this purpose, a study was carried out with a positivist approach, at a descriptive level with a non-experimental cross section. A survey was applied to 20 patients receiving their oncological treatment within the Solca Portoviejo facilities and 20 surveys to family members or caregivers who were accompanying these patients. The results made it possible to verify that the family conditions that favor the permanence in the treatment accompaniment in an oncological family member is due to the existence of the strengthening in family, social relationships, good economic status, emotional stability in the members of the family group. Oncological patients were seen arriving alone to receive their treatment and even came for an examination or medical appointment and presented without any companion. It is important to highlight that the family conditions that favor the permanence of accompaniment in the treatment of cancer patients, is a radical commitment and responsibility that families must have to cope with the patient's disease.